2013
DOI: 10.1177/1721727x1301100217
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor Beta 1 and Vascular Endothelial Growth Factor Levels in the Pathogenesis of Periodontal Disease

Abstract: Periodontal disease is characterized by inflammation and bone loss. The balance between inflammatory mediators and their counter-regulatory molecules may be fundamental for determining the outcome of immune pathology of periodontal disease. Cytokines play crucial roles in the maintenance of tissue homeostasis, a process which requires a delicate balance between anabolic and catabolic activities. In particular, two families of growth factors-such as transforming growth factor-β1 (TGF-β1) and vascular endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…Moreover, oral mucosal epithelial cells (i.e., oral keratinocytes) actively participate in immune response and inflammation through the secretion of a variety of cytokines, chemokines, growth factors, and neuropeptides, which are all involved in periodontal pathogenesis (Hedges et al , ; Sfakianakis et al , ). There are a number of factors promoting leukocyte recruitment, such as bacterial metabolites, cytokines, metalloproteases, growth factors, chemokines, lipid mediators, and other enzymes (Graves and Cochran, ; Matarese et al , , , ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, oral mucosal epithelial cells (i.e., oral keratinocytes) actively participate in immune response and inflammation through the secretion of a variety of cytokines, chemokines, growth factors, and neuropeptides, which are all involved in periodontal pathogenesis (Hedges et al , ; Sfakianakis et al , ). There are a number of factors promoting leukocyte recruitment, such as bacterial metabolites, cytokines, metalloproteases, growth factors, chemokines, lipid mediators, and other enzymes (Graves and Cochran, ; Matarese et al , , , ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the age of disease onset should also be kept in mind. In fact, periodontitis is an inflammatory disease [ 4 , 5 ] typically in the adult different from implant and peri implant diseases and which seems to be a disease in which the onset is still not well defined at this time and the present epidemiological studies are not providing more precise data on it [ 6 , 7 ].…”
Section: The Role Of Periodontologymentioning
confidence: 99%
“…The expression of MPO was strongly associated in the gingival tissue and endothelial cells during periodontitis [14]. More specifically, a clinical study found that, in gingival crevicular fluid, MPO increased with the progression of the periodontitis, and also that MPO was involved in the regulation of IL-1b expression in gingival tissues [15,16].…”
Section: Introductionmentioning
confidence: 99%